2020
DOI: 10.48550/arxiv.2007.10611
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Source Data for the Focus Area Maturity Model for API Management

Max Mathijssen,
Michiel Overeem,
Slinger Jansen

Abstract: We define API Management as an activity that enables organizations to design, publish and deploy their APIs for (external) developers to consume. API Management capabilities such as controlling API lifecycles, access and authentication to APIs, monitoring, throttling and analyzing API usage, as well as providing security and documentation. These capabilities are often implemented through an integrated platform. This data set describes the API Management Focus Area Maturity Model (API-m-FAMM). In a structured m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…By decoupling API management processes and topics from commercial platforms, the API-m-FAMM offers the academic community a de-commercialized overview of the topic that was developed by using insights from both literature as well as the industry. Secondly, this work provides a detailed description of the construction of a focus area maturity model through the published source data [33], that researchers can use as an example in future works. Thirdly, this work has shown that [21]'s methodology for maturity model development may be incorporated with DSR, utilizing [32]'s card sorting technique to perform maturity level assignments, conducting multiple evaluation cycles, and utilization of criteria used for DSR artifact evaluation introduced by Prat et al [40].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…By decoupling API management processes and topics from commercial platforms, the API-m-FAMM offers the academic community a de-commercialized overview of the topic that was developed by using insights from both literature as well as the industry. Secondly, this work provides a detailed description of the construction of a focus area maturity model through the published source data [33], that researchers can use as an example in future works. Thirdly, this work has shown that [21]'s methodology for maturity model development may be incorporated with DSR, utilizing [32]'s card sorting technique to perform maturity level assignments, conducting multiple evaluation cycles, and utilization of criteria used for DSR artifact evaluation introduced by Prat et al [40].…”
Section: Discussionmentioning
confidence: 99%
“…We use these versions to reference to a certain point in the construction of the model. A full description of the changes made during the different phases is available through the source data [33]. The source data also details the dependencies between the different practices.…”
Section: Research Approachmentioning
confidence: 99%
See 2 more Smart Citations